ASUHAN KEPERAWATAN KELUARGA BAPAK S KHUSUSNYA IBU S DENGAN TUBERKULOSIS PARU DI RT 02 RW 07 KELURAHAN LIMO KECAMATAN LIMO KOTA DEPOK - Rima Siti Fadila (2023)
Pulmonary tuberculosis is a long-term infectious disease caused by Mycobacterium tuberculosis which attacks the lung parenchyma. This research was conducted to analyze the application of financial care to Mr. S's family, especially Mrs. S with tuberculosis lungs including reconstruction assessment, reconstruction diagnosis, intervention interventions, reconstruction implementation, and renovation evaluation. The design used is a descriptive design using the case study method. The main problem that arose in Mr. S's family was ineffective health care related to the inability of the family to recognize the problem. After taking action for 2x30 minutes by providing education on Clean and Healthy Behavior (PHBS) about the ethics of acquiring coughs and how to get rid of phlegm which really results in a compilation evaluation resolved with the aim of the specified outcome criteria. The application of financing costs to Mr. S's family, especially Mrs. S with Pulmonary TB, achieved the expected results due to good cooperation between nurses and patients and other health teams. Keywords: Family poverty care, Health maintenance, Pulmonary tuberculosis